2020
DOI: 10.18632/genesandcancer.198
|View full text |Cite
|
Sign up to set email alerts
|

Loss of TRP53 (p53) accelerates tumorigenesis and changes the tumor spectrum of SJL/J mice

Abstract: Known as the guardian of the genome, transformation-related protein 53 (TRP53)is a well -known tumor suppressor. Here, we describe a novel TRP53 deficient mouse model on a tumor prone background-SJL/J mice. The absence of TRP53 (TRP53 nullizygosity) leads to a shift in the tumor spectrum from a non-Hodgkin's-like disease to thymic lymphomas and testicular teratomas at a very rapid tumor onset averaging ~12 weeks of age. In haplotype studies, comparing tumor prone versus tumor resistant Trp53 null mouse strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…For instance in GEMMs (GeneScally Engineered Mouse Models), studies have shown differences among inbred Trp53-deficient strains in the length of Sme required for the development of malignancy: In the 129S1/SvImJ Trp53-/and C57BL6/J Trp53-/-(p53 null) strains, mice develop neoplasias between 18-20 weeks (Donehower et al, 1992;Jacks et al, 1994;Olive et al, 2004). However, BALB/cJ Trp53-/mice show neoplasias by 15 weeks, and in our studies of the tumor-prone SJL/J Trp53-/-, mice have neoplasias by 12 weeks (Branca et al, 2020;Kuperwasser et al, 2000). One would predict that a null mutaSon that completely removes the Trp53 protein (p53 in human) ¾a criScal tumor suppressor and apoptosis regulator¾would not be influenced by the strain background, since cell-cycle and apoptosis genes are conserved among mouse strains (Lozano and Levine, 2016) .…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…For instance in GEMMs (GeneScally Engineered Mouse Models), studies have shown differences among inbred Trp53-deficient strains in the length of Sme required for the development of malignancy: In the 129S1/SvImJ Trp53-/and C57BL6/J Trp53-/-(p53 null) strains, mice develop neoplasias between 18-20 weeks (Donehower et al, 1992;Jacks et al, 1994;Olive et al, 2004). However, BALB/cJ Trp53-/mice show neoplasias by 15 weeks, and in our studies of the tumor-prone SJL/J Trp53-/-, mice have neoplasias by 12 weeks (Branca et al, 2020;Kuperwasser et al, 2000). One would predict that a null mutaSon that completely removes the Trp53 protein (p53 in human) ¾a criScal tumor suppressor and apoptosis regulator¾would not be influenced by the strain background, since cell-cycle and apoptosis genes are conserved among mouse strains (Lozano and Levine, 2016) .…”
Section: Introductionmentioning
confidence: 62%
“…Together, these results suggest that underlying geneSc differences among the mouse strains influence the Sme and type of cancer development irrespecSve of the iniSaSng mutaSon (Branca et al, 2020).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Of note, the master regulators found in CD4 + T cells in this study are not necessarily involved exclusively in gut inflammation. Some of these master regulators might be related to many other processes, especially those that were not differentially expressed, including Trp53 and Ar1 , which are known to be cell cycle master regulators 35 , 36 . Another limitation is that this study was conducted only with females since male mice behave highly aggressive when housed in groups 37 .…”
Section: Discussionmentioning
confidence: 99%